'No Solution to the Immediate Crisis': The Uncertain Political Economy of Energy Conservation in 1970s Britain. (November 2022) - Turnbull, Thomas
Abstract : This article traces one aspect of Britain's approach to the political economy of energy conservation. It focuses on the forecasting work of Royal Dutch Shell and the deliberations of the Heath government. In the late 1960s, the oil major Shell predicted that oil-producing states would impose an embargo on oil-consuming states. Energy conservation policies would be necessary. In tracing the reception of Shell's 'crisis' scenario and its proposed resolution, this article details how these ideas were received by Edward Heath's Conservative government, particularly its 'think-tank', the Central Policy Review Staff. In the short term, interventionist policies were proposed so as to demonstrate Britain's ability to operate without ever-increasing oil consumption, while in the long term the idea was that the energy-saving capacities of a freely-operating market could address the problem. The article recounts the confusion these proposed conservation policies provoked, and how the second idea gradually coalesced and ultimately outlasted the Heath government, providing one justification for the eventual privatisation of Britain's formerly nationalised energy industries.